2012
DOI: 10.5223/pghn.2012.15.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-Esophageal Reflux Disease in Healthy Older Children and Adolescents

Abstract: Gastro-esophageal reflux disease (GERD) in otherwise healthy older children and adolescents is commonly encountered in pediatric clinics and poses a complex treatment problem involving changes of diets and lifestyle. After an initial history taking and a physical examination, typical symptoms of GERD in older children and adolescenct are initially treated with the trials of acid suppressants. With an increase of severe cases, more and more GERD children have been evaluated with endoscopy, which helps to deline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 44 publications
1
9
0
11
Order By: Relevance
“…It is reported that 5-8.2% of children aged between 10 and 17 years old in the US had at least once had GERD symptoms, while a GERD diagnosis was made in 10.9/1000 patients in the UK. Furthermore, in adult studies, GERD symptoms in Asian countries were below 5%, while they were 10-20% in North America and Western European countries (8). It is reported that the GERD incidence in infants is 12.3% in North America and below 1% in older children (9).…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that 5-8.2% of children aged between 10 and 17 years old in the US had at least once had GERD symptoms, while a GERD diagnosis was made in 10.9/1000 patients in the UK. Furthermore, in adult studies, GERD symptoms in Asian countries were below 5%, while they were 10-20% in North America and Western European countries (8). It is reported that the GERD incidence in infants is 12.3% in North America and below 1% in older children (9).…”
Section: Epidemiologymentioning
confidence: 99%
“…Particularly, globus sensation and throat clearing movements in older children are important with respect to regurgitation. Respiratory system symptoms related with gastroesophageal reflux may often be related with diseases such as asthma or laryngitis and sinusitis (1,6,8). The coexistence of asthma and GER has been known for many years.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations